TRANSFORMASI DIRI MELALUI NARASI: KAJIAN KEPUSTAKAAN ATAS TEKNIK KONSELING BIBLIOTERAPI - Oktarizal Drianus; Siti Nuraisah (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2020)
This study aims to describe that the narrative power of a text has a psychological impact on its readers. Reading narrative texts can be an inexpensive and possible therapy, namely as bibliotherapy. This research uses a literature study approach. The analysis of bibliotherapy-related texts was carried out to find the significance, strengths, weaknesses, obstacles, and challenges of practicing bibliotherapy. The findings include 1). Psychologically, the narrative text has the potential as a means of self-transformation of the reader subject; 2) Bibliotherapy may be done in counseling practice both individually and in groups; 3) Bibliotherapy is a technique that has advantages in terms of budget efficiency, easy to apply in a certain school or community settings; 4) Bibliotherapy depends on the depth of reflection between the interpreter subject and the art-skills of the interpreter-counselor to determine the interlocutory world so that self-transformation through the meaning of the narrative text becomes effective.